2003
DOI: 10.1016/s0168-6496(02)00374-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal microbial community shifts observed following oral administration of a Lactobacillus fermentum strain to mice

Abstract: The indigenous gastrointestinal microbiota acts as an integral defense against the colonisation of orally introduced microbes. Whilst this can be important in host protection, some introduced species, including lactobacilli, can have a positive impact on existing microbial communities. The interaction of a candidate probiotic strain of Lactobacillus fermentum within the gastrointestinal tract was monitored in a mouse model and its effect on the indigenous microbiota observed. L. fermentum KLD was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Some previous studies have also demonstrated that feeding rats with probiotics, prebiotics or synbiotics promoted increases of bifidobacteria population at different locations in the rat GIT (Lesniewska et al, 2006;Montesi et al, 2005;Vasquez et al, 2009). Similar results have been also found in other rodent models (Kumar et al, 2008;Plant et al, 2003). Total bifidobacteria counts obtained in our study by using qPCR were in the same order of that reported for rat faecal samples by other authors (Delroisse et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Some previous studies have also demonstrated that feeding rats with probiotics, prebiotics or synbiotics promoted increases of bifidobacteria population at different locations in the rat GIT (Lesniewska et al, 2006;Montesi et al, 2005;Vasquez et al, 2009). Similar results have been also found in other rodent models (Kumar et al, 2008;Plant et al, 2003). Total bifidobacteria counts obtained in our study by using qPCR were in the same order of that reported for rat faecal samples by other authors (Delroisse et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Owing to its sequence variability, the V3 region of the 16S rRNA gene might give sufficient information and might permit the discrimination of bands with a single run of a wide denaturant gradient. Hence, until recently, this short sequence has been used to assess the biodiversity of environmental samples by DGGE (Kurisu et al 2002;Plant et al 2003). For this reason, it was also used in this study.…”
Section: Analysis Of Biofilm Microbial Community Structure By Pcr-dggementioning
confidence: 99%
“…These organisms may belong to at least 400 different bacterial species, although it is thought that 99% of the total community consists of only 30–40 species [1]. The microbial activity of this community has an important metabolic and protective function in the GI‐tract and thus plays a major role in the nutrition and health of the host [2,3]. The genera that are considered to be predominant in the large bowel include Bacteroides , Eubacterium , Clostridium , Ruminococcus , Bifidobacterium and Fusobacterium [4].…”
Section: Introductionmentioning
confidence: 99%